Joint Loading Modality: Its Application to Bone Formation and Fracture Healing - Zhang, Ping (2007)
Sports related injuries such as impact and stress fractures often require a rehabilitation program to stimulate bone formation and accelerate fracture healing. This review introduces a recently developed joint loading modality and evaluates its potential applications to bone formation and fracture healing in post-injury rehabilitation. Bone is a dynamic tissue whose structure is constantly altered in response to its mechanical environments. Indeed, many loading modalities can influence the bone remodeling process. The joint loading modality is, however, able to enhance anabolic responses and accelerate wound healing without inducing significant in situ strain at the site of bone formation or fracture healing. This review highlights the unique features of this loading modality and discusses its potential underlying mechanisms as well as possible clinical applications.